Awakening Africa's Sleeping Giant : Prospects for Commercial Agriculture in the Guinea Savannah Zone and Beyond - World Bank (World Bank, 2012)
This report summarizes the findings of the study on Competitive Commercial Agriculture for Africa (CCAA). The objective of the CCAA study was to explore the feasibility of restoring international competitiveness and growth in African agriculture through the identification of products and production systems that can underpin rapid development of a competitive commercial agriculture. The CCAA study focused on the agricultural potential of Africa's Guinea Savannah zone, which covers about 600 million hectares in Africa, of which about 400 million hectares can be used for agriculture, and of which less than 10 percent are cropped. The African Guinea Savannah is one of the largest underused agricultural land reserves in the world. In terms of its agro climatic features, the land is similar to that found in the Cerrado region of Brazil and in the Northeast Region of Thailand, with medium-to-high agricultural potential but also significant constraints in the form of infertile soils and variable rainfall. Based on a careful examination of the factors that contributed to the successes achieved in Brazil and Thailand, as well as comparative analysis of evidence obtained through detailed case studies of three African (Mozambique, Nigeria, and Zambia) countries. This report argues that opportunities abound for farmers in Africa to regain international competitiveness, especially in light of projected stronger demand in world markets for agricultural commodities over the long term.